Balance Alterations Before ACL Surgery and After Rehabilitation (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2011)
Knee anterior cruciate ligament (ACL) is one of the most often injured knee anatomical structures. There are few studies about balance after ACL rupture, but all results are controversial [1, 2, 3]. Our primary aim was to determine the static and dynamic balance changes before ACL surgery and after rehabilitation. Goals of the study: 1) to investigate and to compare static balance before ACL surgery and after rehabilitation; 2) to investigate and to compare dynamic balance before ACL surgery and after rehabilitation. Ten untrained males participated in this study after ACL rupture (mean ± SD, age 28.4 ± 8.1 years, height – 179.8 ± 8.5 cm, weight – 76.0 ± 14.0 kg). The study was performed in the Lithuanian Academy of Physical Education in the Sports and Movements Science Centre. All subjects where tested before ACL surgery and after 3 months of rehabilitation. Two weeks after the surgery the following rehabilitation was applied: physiotherapy, massage and physiotherapy in the water (3 times per week, 16 times in total). Following these procedures rehabilitation was continued with muscle strength training exercises in a gym. Balance was measured when participant stood on a KISTLER balance platform with open eyes, looking directly into the selected point 2 m away at the eye level, hands on hips. Balance within 20 s while standing on one leg and balance within 15 s after one leg hop for both healthy and ACL ruptured legs were measured. The results showed that standing on ACL ruptured leg before surgery and after rehabilitation the oscillations were not significantly different, but standing on the healthy leg after rehabilitation significantly improved. Test results after one leg hop on ACL ruptured leg showed that oscillations were significantly greater after rehabilitation. Conclusions: 1. After rehabilitation one leg static balance improved only in non-injured leg. 2. After rehabilitation one leg dynamic balance decreased in injured leg, but increased in non-injured leg.Keywords: anterior cruciate ligament, rehabilitation, static balance, dynamic balance